2006
DOI: 10.1590/s1516-89132006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and ecological interactions between reintroduced golden lion tamarins (Leontopithecus rosalia Linnaeus, 1766) and introduced marmosets (Callithrix spp, Linnaeus, 1758) in Brazil's Atlantic Coast forest fragments

Abstract: Marmosets (Callithrix spp.) have been introduced widely in areas within

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 33 publications
1
36
0
11
Order By: Relevance
“…Saimiri sciureus showed a significant degree of tolerance. The territorial behaviors that we observed between the groups of C. jacchus and S. sciureus have also been shown in a previous study by Ruiz-Miranda et al (2006). In that case, C. jacchus was the introduced species and the native species was Leontopithecus rosalia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Saimiri sciureus showed a significant degree of tolerance. The territorial behaviors that we observed between the groups of C. jacchus and S. sciureus have also been shown in a previous study by Ruiz-Miranda et al (2006). In that case, C. jacchus was the introduced species and the native species was Leontopithecus rosalia.…”
Section: Discussionsupporting
confidence: 88%
“…The introduction of exotic or allochthonous species corresponds to the accidental or intentional release of individuals into an area where they usually do not occur (Moura-Brito and Patrocínio 2006;Ruiz-Miranda et al 2006). The introduced species may assume the role of competitors, reducing food resources and potentially introducing diseases to the new environment (Primack and Rodrigues 2001;MouraBrito and Patrocínio 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ruiz-Miranda et al [24] showed that white-tufted-ear marmoset (C. jacchus) and the black-tufted-ear marmoset (C. penicillata) compete for food with the golden-lion tamarin, L. rosalia. Both Callithrix species occur with the golden lion tamarin in many parts of the tamarin's geographical range [27].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Pelo contrário, a ação antrópica sobre os animais e seu habitat (principalmente mata atlântica e cerrado) tem gerado a disseminação destes primatas para regiões onde estes passam a ser invasores, colocando em risco outras espécies (Ruiz-Miranda et al 2006, Morais Jr 2010.…”
Section: Introductionunclassified